COVID-19 Suicide Survivors—A Hidden Grieving Population - Pinto, Sara; Soares, Joana; Silva, Alzira; Curral, Rosário; Coelho, Rui (Frontiers in Psychiatry, 2020)
Present time has been dominated by the COVID-19 pandemic. People are grieving several non-death related situations: the loss of a job, of a status, of a role, of their life. Restrictive measures and uncertainty about the future makes individuals vulnerable to feelings of hopelessness and helplessness. Mental health support has been hindered and teams are reinventing themselves to reach people in need. Nevertheless, decompensation of previous psychiatric disorders, increasing levels of depression and anxiety, economical handicaps and fear of the infection, are prompting several cases of COVID-19 related suicides worldwide. Every suicide affects between 5 to 80 individuals, which are known as suicide survivors. Suicide grief is particularly challenging, with rates of complicated grief as high as 40%. Suicide survivors are at increased risk of developing depression, anxiety disorders and of suicidal behaviors. Moreover, feelings of guilt and shame, as well as social stigma, are major obstacles for them to reach form help. This article aims to review the existing literature on COVID-19 related suicides, complicated grief in suicide survivors and highlight modifiable risk factors for both conditions, as well as propose some public health measures to reduce the impact of the pandemic context on self-inflicted harm and its consequences on families, friends and the community. Obstacles to access to mental health support need to be overcome through the use of technology. Technicians should actively approach populations more vulnerable to develop suicidal ideation. Social media have the obligation to provide accurate an non-sensationalistic information. Families and friends should maintain social proximity, despite the need for physical distancing. When a suicide death occurs, police forces and health staff should be prepared to share the news with the family using an empathic and humane approach and providing psychological support. Funerals, memorials and other services should be held as much as possible. Closer contacts should be signalized and closely followed in order to detect the need for specific interventions. Help seeking behaviors should be promoted. Additionally, people should be educated on suicide and its impacts, in order to reduce stigma